Self-assembly of nanostructured PbS for solar photovoltaic applications - Hawaldar, Ranjit R.; Kanade, K. G.; Patil, K. R.; Sathaye, S. D.; Mulik, Uttam P.; Amalnerkar, Dinesh P. (Materials Chemistry and Physics, 2005)
In the present communication, the self-assembly of nanocrystalline PbS at the liquid-liquid interface is reported. The PbS nanocrystals were, subsequently, transformed in the form of thin films by dip coating. The resultant Q-PbS films were characterized by SEM-EDAX, TEM-SAED, XRD, XPS and UV-vis Spectroscopy. Pyramidal features at the nanometer scale, preferred orientation along (2 2 0) and (4 0 0) planes of cubic structure and a sharp excitonic peak at 656 run are the salient aspects of this work. The band-gap of the order of 1.8 eV (associated with the excitonic feature) is ideally suited for solar photovoltaic applications. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: Liquid-liquid interface; nanopyramid; Nanostructures; PbS

One-step in situ synthesis of NHx-adsorbed rhodium nanocrystals at liquid-liquid interfaces for possible electrocatalytic applications - Patil, V. S.; Krishna, S. R.; Hawaldar, Ranjit R.; Gaikwad, A. B.; Sathaye, S. D.; Patil, K. R. (Journal of Colloid and Interface Science, 2011)
Nearly monodisperse rhodium nanoparticles with adsorbed NHx were synthesized at the CCl4-water interface. The presence of NHx-adsorbed species was confirmed by energy-dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS) studies. The synthesis of controlled size 2-38 nm rhodium particles was studied as a function of reducing agent concentration by transmission electron microscopy (TEM). HRTEM confirmed the formation of rhodium nanoparticles having fringe spacing consistent with reported Rh (1 1 1) planes. The continuity of these films over an area of 1 x 1 pm was revealed by atomic force microscopy (AFM) studies. The electrocatalytic application of these nanostructure Rh-NHx), thin films for formaldehyde oxidation in 0.5 M NaOH was investigated by cyclic voltammetry. The Rh nanoparticles formed by the present strategy are expected to be useful for other catalytic applications also. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Hydrazine hydrate; Liquid-liquid interface; Nanoparticles; Rhodium; Thin films